2023
DOI: 10.1002/med.21986
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant peptides, the guardian of life from oxidative stress

Yiyun Zhu,
Kang Wang,
Xinyi Jia
et al.

Abstract: Reactive oxygen species (ROS) are produced during oxidative metabolism in aerobic organisms. Under normal conditions, ROS production and elimination are in a relatively balanced state. However, under internal or external environmental stress, such as high glucose levels or UV radiation, ROS production can increase significantly, leading to oxidative stress. Excess ROS production not only damages biomolecules but is also closely associated with the pathogenesis of many diseases, such as skin photoaging, diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 561 publications
0
14
0
Order By: Relevance
“…It is primarily concerned with the removal of free radical species such as hydrogen peroxide, superoxide radicals, and alkoxy radicals. It also maintains the membrane protein thiol and works as a substrate for glutathione peroxidase and GST (Prakash et al, 2001;Zhu et al, 2023). Our results showed that the extract caused an increase in GSH levels compared to the negative control group.…”
Section: Flower-containing Seeds and Leaves Extract Of Plant DV Enhan...mentioning
confidence: 56%
“…It is primarily concerned with the removal of free radical species such as hydrogen peroxide, superoxide radicals, and alkoxy radicals. It also maintains the membrane protein thiol and works as a substrate for glutathione peroxidase and GST (Prakash et al, 2001;Zhu et al, 2023). Our results showed that the extract caused an increase in GSH levels compared to the negative control group.…”
Section: Flower-containing Seeds and Leaves Extract Of Plant DV Enhan...mentioning
confidence: 56%
“…ROS is generated with ischemia and then targets the normal physiologic functions of cells by damaging the structures of proteins, lipids, and even DNA ( Zhu, et al, 2024 ). As well, oxidative stress promotes cardiac ischemia-reperfusion injury and was implicated in pro-inflammatory responses and apoptosis, both of which worsen myocardial cell injury ( Patel and Karch, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) and free radicals are beneficial byproducts to human health. However, an excess of ROS and free radicals can cause serious oxidative damage to a cell’s structure or function, which can contribute to the onset of a number of diseases, including diabetes, aging, and neurodegenerative illnesses [ 102 , 103 ]. Hydrolyzed peptides from egg proteins are believed to be potent antioxidants that can either scavenge reactive oxygen species (ROS) or stop ROS from being produced [ 104 ].…”
Section: Biological Activities Of Hen Egg-derived Peptidesmentioning
confidence: 99%